2013
DOI: 10.1002/eji.201343451
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Treg cells/T effector function by GITR signaling is context–dependent

Abstract: Treg cells express high levels of the glucocorticoid-induced tumor necrosis factorrelated receptor (GITR), IntroductionThe glucocorticoid-induced tumor necrosis factor-related receptor (GITR), a member of the TNF receptor superfamily (TNFRSF) is expressed at high levels on the majority of freshly explanted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 35 publications
4
62
0
1
Order By: Relevance
“…Despite this general improvement of the autoimmune phenotype it should be noted that even B-cell-deficient Scurfy mice eventually died, suggesting that other antibody independent pathways are critical for the full-blown autoimmune phenotype. This is in line with studies showing that the transfer of T helper cells depleted for Tregs into B-and T-cell-deficient recombination activating gene (Rag) −/− mice can induce a Scurfy-like autoimmune pathology (30). Apart from B cells, T cells, and T-cell-derived cytokines are also critical to control the activation of innate immune effector cells, such as monocytes and macrophages, which might be responsible for the delayed inflammation and the death of affected animals (21).…”
Section: Therapeutic Depletion Of B Cells Interferes With Autoimmunitsupporting
confidence: 88%
“…Despite this general improvement of the autoimmune phenotype it should be noted that even B-cell-deficient Scurfy mice eventually died, suggesting that other antibody independent pathways are critical for the full-blown autoimmune phenotype. This is in line with studies showing that the transfer of T helper cells depleted for Tregs into B-and T-cell-deficient recombination activating gene (Rag) −/− mice can induce a Scurfy-like autoimmune pathology (30). Apart from B cells, T cells, and T-cell-derived cytokines are also critical to control the activation of innate immune effector cells, such as monocytes and macrophages, which might be responsible for the delayed inflammation and the death of affected animals (21).…”
Section: Therapeutic Depletion Of B Cells Interferes With Autoimmunitsupporting
confidence: 88%
“…Mixed fetal liver chimeras of WT and Napa hyh/hyh showed further reduced percentages of Napa hyh/hyh Foxp3 Tregs in the thymus (Figure 2B) as well as peripheral lymphoid tissues (Figure 2C) and Napa hyh/hyh Foxp3 Tregs consistently showed lower surface expression of CD44 (Figure 2D) and GITR (Figure 2E). These data suggest additional potential defects in the homing (Luo et al, 2016) and in vivo expansion of Foxp3 Tregs (Ronchetti et al, 2015; Ephrem et al, 2013; Liao et al, 2010). Indeed, lamina propria of Napa hyh/hyh chimeras showed further reduced numbers of Foxp3 Tregs (Figure 2F).…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, a series of genetic factors have been documented in association with initiation and development of CWP, including genes modulating inflammatory and immune responses [6,8]. Interaction of GITR with GITRL could up-regulate conventional T cell responses and down-regulate T reg suppressor activity, thus upset the balance and result in a breakdown of autoimmune response and immunological tolerance [23,31]. Cuzzocrea et al [26] reported that mice lacking GITR(GITR − / − ) in a bleomycin-induced lung fibrosis model had a decreased lung injury and a decreased production of fibrogenic cytokines such as IL-1␤ and TNF-␣ which were clearly involved in the pathogenesis of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is constitutively expressed at high levels in CD4 + T reg cells, and at low levels in resting CD4 + T eff cells, but strongly up-regulated upon T eff cell activation [16,21,22]. When activated, GITR promotes activation and differentiation of CD4 + T eff cells, but down-regulates suppressor activity of CD4 + T reg cells [23], thus modulates the immune responses. Expression of GITR has also been detected in nonlymphoid cells, such as PMNs, macrophages, and been induced by steroids, as well as by other cell-activating stimuli such as proinflammatory conditions [24].…”
Section: Introductionmentioning
confidence: 99%